A plastic admixture for vacuum extrusion molding of ridged vanadium tailings and preparation method thereof
By developing a plastic additive for spinal vanadium tailings, the problems of low plasticity of vanadium tailings and easy product fracture are solved, and the efficient vacuum extrusion of vanadium tailings is achieved and the crack resistance and compression resistance of vanadium tailings is improved, and the resource utilization and environmental protection of vanadium tailings is promoted.
Patent Information
- Application Number
- CN202310238387.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-13
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-03-13
AI Technical Summary
The vanadium tail slag has low plasticity and cannot meet the requirements of the vacuum extrusion process. At the same time, the products after vacuum extrusion are prone to fracture and cannot meet the crack and compressive resistance indicators of the building materials industry.
A plastic admixture for spinal vanadium tailings is developed, including fibers, water retention agents, plasticizers and coupling agents, to improve the plasticity of vanadium tailings and enhance its crack and compressive resistance through the interaction of polar groups and the distribution of fibers.
The plasticity index of vanadium tailings is significantly improved, meeting the requirements of vacuum extrusion equipment, and at the same time, the crack resistance and compressive resistance of extruded plates are enhanced, the comprehensive utilization of vanadium tailings is realized, and environmental pollution and waste of land resources are reduced.
Smart Images

Figure BDA0004123914420000021 
Figure BDA0004123914420000031
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic admixtures, in particular to a plastic admixture used for vacuum extrusion molding of ridged vanadium tailings and a preparation method thereof. Background Art
[0002] At present, the total proven vanadium metal reserves in the world are about 22 million tons, of which my country's total vanadium metal reserves are about 9.5 million tons, accounting for about 43% of the world's reserves. The global consumption of vanadium metal has exceeded 100,000 tons each year. The huge market demand will inevitably lead to the vigorous development of the vanadium extraction industry.
[0003] The currently known vanadium metal extraction processes will produce a large amount of solid waste - vanadium tailings. The current treatment method for vanadium tailings is mainly stockpiling. On the one hand, the large amount of tailings storage occupies arable land and causes waste of land resources; on the other hand, the long-term accumulation of heavy metals, its radioactivity and toxicity will not only cause pollution and damage to the surrounding environment, but also cause great harm to human health.
[0004] The current research hotspot is to use the vacuum extrusion process to produce vanadium tailings into products that can be used to make assembled building panels, turning waste into treasure and realizing the comprehensive utilization of resources. However, the vacuum extrusion process has special requirements for the plasticity of raw materials. Materials with no plasticity or too low plasticity cannot be vacuum extruded. Vanadium tailings are ridged materials with extremely low plasticity, which are far from meeting the requirements of vacuum extrusion. At present, there are no special admixture products on the market that can meet the vacuum extrusion plasticity requirements of vanadium tailings, and at the same time ensure that the vacuum extruded vanadium tailings panel products meet the relevant anti-cracking and compression resistance indicators of the building materials industry.
[0005] Therefore, obtaining a plastic additive that can be used for vacuum extrusion molding of vanadium tailings is a technical problem that needs to be solved at present. Summary of the invention
[0006] The purpose of the present invention is to provide a plastic additive for vacuum extrusion molding of ridged vanadium tailings and a preparation method thereof, so as to solve the technical problems of low plasticity of vanadium tailings and easy fracture of vacuum extruded products.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] The present invention provides a plastic additive for vacuum extrusion molding of ridged vanadium tailings, comprising the following components in parts by mass:
[0009]
[0010]
[0011] Furthermore, the fibers include one or more of plant fibers, polypropylene fibers and polyvinyl alcohol fibers.
[0012] Furthermore, the fibers include plant fibers, polypropylene fibers, and polyvinyl alcohol fibers in a mass ratio of 1-6:0.2-1.5:0.08-0.2.
[0013] Furthermore, the water retaining agent comprises one or more of cellulose ether, methyl cellulose and hydroxypropyl methyl cellulose.
[0014] Furthermore, the water retaining agent comprises cellulose ether, methyl cellulose and hydroxypropyl methyl cellulose in a mass ratio of 0.2-0.5:0.4-0.9:0.5-0.6.
[0015] Furthermore, the plasticizer comprises one or more of bentonite, polyvinyl amide and polyvinyl alcohol;
[0016] The coupling agent comprises vinyltriethoxysilane and / or aminopropyltriethoxysilane.
[0017] Furthermore, the plasticizer comprises bentonite, polyvinyl amide and polyvinyl alcohol in a mass ratio of 3-6: 0.05-0.1: 0.5-1;
[0018] The coupling agent comprises vinyl triethoxy silane and aminopropyl triethoxy silane in a mass ratio of 0.5-0.8:0.2-0.5.
[0019] The present invention provides a method for preparing a plastic admixture for vacuum extrusion molding of ridged vanadium tailings, comprising the following steps:
[0020] 1) Adding the fibers into water in batches to obtain a paste;
[0021] 2) Mix the water retaining agent, plasticizer and coupling agent with the paste to obtain the plastic admixture.
[0022] Furthermore, in the step 1), the stirring time for each batch of added fibers is independently 15 to 30 minutes, and the stirring rate is independently 15 to 30 r / min.
[0023] Furthermore, in the step 2), the mixing speed is 15 to 30 r / min, and the mixing time is 20 to 40 min.
[0024] Beneficial effects of the present invention:
[0025] The plastic admixture of the present invention is added to the vanadium tailings, and the interaction between the polar groups weakens the interaction between the polymers, thereby increasing the plasticity of the vanadium tailings, so that it can meet the vacuum extrusion requirements. At the same time, the fiber components contained therein can effectively reduce the inherent defects and cracks in the tailings plate, and strengthen the crack resistance and compression resistance, which is the so-called fiber spacing theory. The application of the plastic admixture of the present invention effectively solves the shortcomings of low plasticity of the vanadium tailings and easy fracture of vacuum extruded products, maximizes the resource utilization of the vanadium tailings solid waste, reduces environmental pollution and personnel hazards, and also achieves energy saving and consumption reduction, green development.
[0026] The components of the plastic admixture of the present invention interact with each other. By adjusting and optimizing the dosage ratio of the components, after the plastic admixture is added to the ridged vanadium tailings, the plasticity of the tailings is significantly improved, which can greatly meet the requirements of plastic vacuum extrusion. At the same time, the crack resistance and toughness indicators of the vanadium tailings extruded plate products are guaranteed in the later stage, which has a dual effect.
[0027] Compared with the prior art, the plastic admixture prepared by the present invention can significantly improve the plasticity of the ridged vanadium tailings, improve its thixotropic properties, reduce the loss rate of free water, and reduce the risks of cracking and easy breaking during the later maintenance process, truly achieving the effects of plasticization, water retention, crack resistance, and toughening. The plasticity index of the vanadium tailings can be increased to IP = 7-13, and the 28d compressive strength of the vanadium tailings vacuum extruded plate can reach 5.0MPa, the bending load (plate weight multiple) ≥ 1.5, and the surface density is about 80kg / m 3 . DETAILED DESCRIPTION
[0028] The present invention provides a plastic additive for vacuum extrusion molding of ridged vanadium tailings, comprising the following components in parts by mass:
[0029]
[0030] In the present invention, the content of the fiber is preferably 10 to 30 parts by mass, more preferably 15 to 25 parts by mass, and even more preferably 20 parts by mass.
[0031] In the present invention, the fibers include one or more of plant fibers, polypropylene fibers and polyvinyl alcohol fibers, preferably plant fibers and / or polypropylene fibers.
[0032] In the present invention, the fibers include plant fibers, polypropylene fibers and polyvinyl alcohol fibers in a mass ratio of 1-6: 0.2-1.5: 0.08-0.2, preferably 2-5: 0.5-1.2: 0.1-0.18, and more preferably 3-4: 0.8-1.0: 0.15.
[0033] In the present invention, the fiber is a sheet-like monomer fiber, which is easily dispersed into fiber monofilaments under the action of water immersion and the friction of a mixer, and can effectively reduce the inherent defects and cracks in the vanadium tailings plate product, and play an anti-cracking and strengthening effect.
[0034] In the present invention, the amount of the water retaining agent is preferably 0.8 to 4 parts by weight, more preferably 1 to 3 parts, and more preferably 2 parts.
[0035] In the present invention, the water retaining agent comprises one or more of cellulose ether, methyl cellulose and hydroxypropyl methyl cellulose, preferably cellulose ether and / or methyl cellulose.
[0036] In the present invention, the water retaining agent comprises cellulose ether, methyl cellulose and hydroxypropyl methyl cellulose in a mass ratio of 0.2-0.5:0.4-0.9:0.5-0.6, preferably 0.3-0.4:0.5-0.8:0.55, and more preferably 0.35:0.6-0.7:0.55.
[0037] In the present invention, the amount of the plasticizer is preferably 1 to 35 parts by mass, more preferably 5 to 30 parts by mass, and even more preferably 10 to 20 parts by mass.
[0038] In the present invention, the plasticizer comprises one or more of bentonite, polyvinyl amide and polyvinyl alcohol, preferably bentonite and / or polyvinyl amide.
[0039] In the present invention, the plasticizer comprises bentonite, polyvinyl amide and polyvinyl alcohol in a mass ratio of 3-6: 0.05-0.1: 0.5-1, preferably 4-5: 0.06-0.09: 0.6-0.9, and more preferably 4.5: 0.08: 0.8.
[0040] In the present invention, the role of bentonite in the plasticizer is mainly reflected in its thixotropy. After the bentonite contacts with water, it will form a thixotropic mud similar to a non-Newtonian fluid. When stationary, the bentonite molecules are interconnected to form a network structure, which has a high viscosity for the free mud and a certain bearing capacity, thereby improving the plasticity of the raw material tailings.
[0041] In the present invention, the polyvinyl amide and polyvinyl alcohol molecules in the plasticizer contain -OH groups, and hydrogen bonds can be formed between the molecules. Hydrogen bonds are a relatively strong interaction bond, which can react with polar groups in the vanadium tailings raw material, replace the action between polymer molecules, increase the interaction between the plasticizer and the polymer molecules, thereby weakening the interaction between macromolecules and achieving the purpose of plasticization.
[0042] In the present invention, the amount of the coupling agent is preferably 0.6 to 1.0 part by mass, more preferably 0.7 to 0.9 part, and more preferably 0.8 part.
[0043] In the present invention, the coupling agent comprises vinyl triethoxy silane and / or aminopropyl triethoxy silane, preferably vinyl triethoxy silane.
[0044] In the present invention, the coupling agent comprises vinyl triethoxysilane and aminopropyl triethoxysilane in a mass ratio of 0.5-0.8:0.2-0.5, preferably 0.6-0.7:0.3-0.4, and more preferably 0.65:0.35.
[0045] The present invention provides a method for preparing a plastic admixture for vacuum extrusion molding of ridged vanadium tailings, comprising the following steps:
[0046] 1) Adding the fibers into water in batches to obtain a paste;
[0047] 2) Mix the water retaining agent, plasticizer and coupling agent with the paste to obtain the plastic admixture.
[0048] In the present invention, in the step 1), the stirring time for each batch of added fibers is independently 15 to 30 minutes, preferably 18 to 25 minutes, and more preferably 20 to 22 minutes; the stirring rate is independently 15 to 30 r / min, preferably 18 to 25 r / min, and more preferably 20 to 22 r / min.
[0049] In the present invention, in step 2), the mixing speed is 15 to 30 r / min, preferably 18 to 25 r / min, and more preferably 20 to 22 r / min; the mixing time is 20 to 40 min, preferably 25 to 35 min, and more preferably 30 min.
[0050] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0051] Example 1
[0052] Component dosage of plastic admixture:
[0053] 12 parts of fiber, 1.5 parts of water retaining agent, 24 parts of plasticizer, and 0.6 parts of coupling agent.
[0054] The fibers include plant fibers, polypropylene fibers and polyvinyl alcohol fibers, and the usage ratio of each component is plant fibers: polypropylene fibers: polyvinyl alcohol fibers = 2:0.43:0.15.
[0055] The water retaining agent includes cellulose ether, methyl cellulose and hydroxypropyl methyl cellulose, and the usage ratio of each component is cellulose ether: methyl cellulose: hydroxypropyl methyl cellulose = 0.25: 0.67: 0.57.
[0056] The plasticizer includes bentonite, polyvinyl amide and polyvinyl alcohol, and the usage ratio of each component is bentonite: polyvinyl amide: polyvinyl alcohol=4.5:0.075:0.75.
[0057] The coupling agent includes vinyl triethoxysilane and aminopropyl triethoxysilane, and the usage ratio of each component is vinyl triethoxysilane:aminopropyl triethoxysilane=0.65:0.3.
[0058] Preparation method of plastic admixture:
[0059] Plant fiber is difficult to mix evenly with other substances in the material, so the fiber is added to the water in batches, and the total amount of fiber added is mixed with the total amount of water added at a mass ratio of 1:20. Stir in a blender for 20 minutes at a stirring rate of 20r / min. After the fiber is completely dissolved and forms a paste, start adding it for the second time until all the fibers are added to obtain a paste liquid.
[0060] Add water retaining agent, plasticizer and coupling agent to the above paste in sequence, stirring at 20r / min for 30min, and observe until everything is mixed evenly.
[0061] The prepared plastic admixture and the ridged vanadium tailings were mixed in a mass ratio of 9:1000, aged at room temperature for 24 hours, and then vacuum extruded. The ridged vanadium tailings raw material is the tailings discharged from the vanadium mine in Shangnan County, Shaanxi Province after roasting and acid leaching, which has almost no plasticity.
[0062] Compared with vanadium tailings without plastic admixture, the plasticity index can be increased to IP=13.27 after adding plastic admixture, which fully meets the requirements of vacuum extrusion equipment. After curing, the extruded plate specimen has a 28d compressive strength of 4.5MPa, a bending load (plate weight multiple) ≥1.5, and a surface density of 83kg / m 3 , no cracking.
[0063] Example 2
[0064] Component dosage of plastic admixture:
[0065] Fiber 20 parts, water retaining agent 3.0 parts, plasticizer 16 parts, coupling agent 0.5 parts.
[0066] Among them, the fiber is plant fiber.
[0067] The water retaining agent includes cellulose ether, methyl cellulose and hydroxypropyl methyl cellulose, and the usage ratio of each component is cellulose ether: methyl cellulose: hydroxypropyl methyl cellulose = 0.5: 0.85: 0.5.
[0068] The plasticizer includes bentonite, polyvinyl amide and polyvinyl alcohol, and the usage ratio of each component is bentonite: polyvinyl amide: polyvinyl alcohol=3.0:0.1:0.5.
[0069] The coupling agent includes vinyl triethoxysilane and aminopropyl triethoxysilane, and the usage ratio of each component is vinyl triethoxysilane:aminopropyl triethoxysilane=0.6:0.25.
[0070] The preparation method of the plastic admixture is the same as that of Example 1.
[0071] The prepared plastic admixture is mixed with the ridged vanadium tailings and sand in a mass ratio of 10:1000:15, stirred evenly, aged at room temperature for 24 hours, and then vacuum extruded.
[0072] The above-mentioned ridged vanadium tailings are tailings discharged from the vanadium mine in Shangnan County, Shaanxi Province after roasting and acid leaching, and have almost no plasticity.
[0073] Compared with vanadium tailings without plastic admixture, the plasticity index can be increased to IP=8.39 after adding plastic admixture, which fully meets the requirements of vacuum extrusion equipment. After curing, the extruded plate specimen has a 28d compressive strength of 4.7MPa, a bending load (plate weight multiple) ≥1.5, and a surface density of 79kg / m 3 , no cracking.
[0074] Example 3
[0075] Component dosage of plastic admixture:
[0076] 30 parts of fiber, 2.5 parts of water retaining agent, 12 parts of plasticizer, and 0.8 parts of coupling agent.
[0077] The fibers are plant fibers and polypropylene fibers, and the usage ratio of the plant fibers to the polypropylene fibers is plant fibers: polypropylene fibers = 5:1.2.
[0078] Wherein, the water retaining agent is cellulose ether.
[0079] The plasticizer includes bentonite, polyvinyl amide and polyvinyl alcohol, and the usage ratio of each component is bentonite: polyvinyl amide: polyvinyl alcohol=4.0:0.05:0.6.
[0080] The coupling agent includes vinyl triethoxysilane and aminopropyl triethoxysilane, and the usage ratio of each component is vinyl triethoxysilane:aminopropyl triethoxysilane=0.6:0.25.
[0081] The preparation method of the plastic admixture is the same as that of Example 1.
[0082] The prepared plastic admixture and the ridged vanadium tailings were mixed in a mass ratio of 8:1000, aged at room temperature for 24 hours, and then vacuum extruded. The ridged vanadium tailings raw material is the tailings discharged from the vanadium mine in Shangnan County, Shaanxi Province after roasting and acid leaching, which has almost no plasticity.
[0083] Compared with vanadium tailings without plastic admixture, the plasticity index can be increased to IP=8.55 after adding plastic admixture, which fully meets the requirements of vacuum infrastructure equipment. After curing, the extruded plate specimen has a 28d compressive strength of 4.6MPa, a bending load (plate weight multiple) ≥1.5, and a surface density of 79kg / m 3 , no cracking.
[0084] Example 4
[0085] Component dosage of plastic admixture:
[0086] 30 parts of fiber, 5.0 parts of water retaining agent, 10 parts of plasticizer, and 0.5 parts of coupling agent.
[0087] The fibers are plant fibers and polypropylene fibers, and the usage ratio of the plant fibers to the polypropylene fibers is plant fibers: polypropylene fibers = 3:1.
[0088] The water retaining agent includes methyl cellulose and hydroxypropyl methyl cellulose, and the usage ratio of each component is methyl cellulose: hydroxypropyl methyl cellulose = 0.5: 0.67.
[0089] Wherein, the plasticizer is polyvinyl amide.
[0090] The coupling agent includes vinyl triethoxysilane and aminopropyl triethoxysilane, and the usage ratio of each component is vinyl triethoxysilane:aminopropyl triethoxysilane=0.5:0.3.
[0091] The preparation method of the plastic admixture is the same as that of Example 1.
[0092] The prepared plastic admixture and the ridged vanadium tailings were mixed in a mass ratio of 13:1000, stirred evenly, aged at room temperature for 24 hours, and then vacuum extruded.
[0093] The above-mentioned ridged vanadium tailings are tailings discharged from the vanadium mine in Shangnan County, Shaanxi Province after roasting and acid leaching, and have almost no plasticity.
[0094] Compared with vanadium tailings without plastic admixture, the plasticity index can be increased to IP=8.09 after adding plastic admixture, which fully meets the requirements of vacuum extrusion equipment. After curing, the extruded plate specimen has a 28d compressive strength of 4.9MPa, a bending load (multiple of plate weight) ≥1.5, and a surface density of 80kg / m 3 , no cracking.
[0095] Example 5
[0096] Component dosage of plastic admixture:
[0097] Fiber 32 parts, water retaining agent 4.0 parts, plasticizer 12 parts, coupling agent 0.65 parts.
[0098] The fibers are plant fibers and polypropylene fibers, and the usage ratio of the plant fibers to the polypropylene fibers is plant fibers: polypropylene fibers = 15:4.
[0099] Wherein, the water retaining agent is cellulose ether.
[0100] The plasticizer includes bentonite, polyvinyl amide and polyvinyl alcohol, and the usage ratio of each component is bentonite: polyvinyl amide: polyvinyl alcohol=3.0:0.08:0.8.
[0101] Wherein, the coupling agent is vinyltriethoxysilane.
[0102] The preparation method of the plastic admixture is the same as that of Example 1.
[0103] The prepared plastic admixture and the ridged vanadium tailings were mixed in a mass ratio of 11:1000, stirred evenly, aged at room temperature for 24 hours, and then vacuum extruded.
[0104] The above-mentioned ridged vanadium tailings are tailings discharged from the vanadium mine in Shangnan County, Shaanxi Province after roasting and acid leaching, and have almost no plasticity.
[0105] Compared with vanadium tailings without plastic admixture, the plasticity index can be increased to IP=7.99 after adding plastic admixture, which fully meets the requirements of vacuum extrusion equipment. After curing, the extruded plate specimen has a 28d compressive strength of 5.1MPa, a bending load (plate weight multiple) ≥1.5, and a surface density of 78kg / m 3 , no cracking.
[0106] Example 6
[0107] Component dosage of plastic admixture:
[0108] Fiber 25 parts, water retaining agent 5.0 parts, plasticizer 20 parts, coupling agent 0.6 parts.
[0109] The fibers include plant fibers, polypropylene fibers and polyvinyl alcohol fibers, and the usage ratio of each component is plant fibers: polypropylene fibers: polyvinyl alcohol fibers = 2.8:0.8:0.1.
[0110] The water retaining agent includes cellulose ether, methyl cellulose and hydroxypropyl methyl cellulose, and the usage ratio of each component is cellulose ether: methyl cellulose: hydroxypropyl methyl cellulose = 0.4: 0.5: 0.5.
[0111] The plasticizer includes polyvinyl amide and polyvinyl alcohol, and the usage ratio of polyvinyl amide to polyvinyl alcohol is polyvinyl amide: polyvinyl alcohol = 0.1:0.5.
[0112] Wherein, the coupling agent is vinyltriethoxysilane.
[0113] The preparation method of the plastic admixture is the same as that of Example 1.
[0114] The prepared plastic admixture and the ridged vanadium tailings were mixed in a mass ratio of 10:1000, stirred evenly, aged at room temperature for 24 hours, and then vacuum extruded.
[0115] The above-mentioned ridged vanadium tailings are tailings discharged from the vanadium mine in Shangnan County, Shaanxi Province after roasting and acid leaching, and have almost no plasticity.
[0116] Compared with vanadium tailings without plastic admixture, the plasticity index can be increased to IP=8.62 after adding plastic admixture, which fully meets the requirements of vacuum extrusion equipment. After curing, the extruded plate specimen has a 28d compressive strength of 4.3MPa, a bending load (multiple of plate weight) ≥1.5, and a surface density of 81kg / m 3 , no cracking.
[0117] It can be seen from the above embodiments that the present invention provides a plastic admixture for vacuum extrusion molding of ridged vanadium tailings and a preparation method thereof. The plastic admixture of the present invention solves the problem that the ridged vanadium tailings have low plasticity and cannot be vacuum extruded, realizes the transformation of vanadium tailings vacuum extrusion assembled plates, and at the same time enhances the crack resistance and compression resistance of vanadium tailings after extrusion, realizes the comprehensive utilization of vanadium tailings, saves energy and reduces consumption, and turns waste into treasure; at the same time, it reduces the occupation of land resources by tailings storage, reduces the risk of environmental pollution and personnel safety hazards, and realizes green, energy-saving, environmentally friendly and resource-based solid waste utilization.
[0118] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A plastic admixture for vacuum extrusion molding of ridged vanadium tailings, characterized in that: The composition includes the following components in parts by weight: Fiber 10-30 parts; Water retaining agent 0.5~5 parts; Plasticizer 10~20 parts; Coupling agent 0.5~1.2 parts; The fibers include plant fibers, polypropylene fibers, and polyvinyl alcohol fibers in a mass ratio of 1-6:0.2-1.5:0.08-0.2; The water retaining agent comprises cellulose ether, methyl cellulose and hydroxypropyl methyl cellulose in a mass ratio of 0.2-0.5:0.4-0.9:0.5-0.6; The plasticizer comprises bentonite, polyvinyl amide and polyvinyl alcohol in a mass ratio of 3-6:0.05-0.1:0.5-1; The coupling agent comprises vinyl triethoxy silane and aminopropyl triethoxy silane in a mass ratio of 0.5-0.8:0.2-0.
5.
2. The method for preparing the plastic admixture for vacuum extrusion molding of ridged vanadium tailings according to claim 1, characterized in that: The following steps are involved: 1) Add the fiber into water in batches to obtain a paste; 2) Mix the water retaining agent, plasticizer and coupling agent with the paste to obtain the plastic admixture.
3. The method for preparing a plastic admixture for vacuum extrusion molding of ridged vanadium tailings according to claim 2, characterized in that: In the step 1), the stirring time for each batch of added fibers is independently 15-30 minutes, and the stirring rate is independently 15-30 r / min.
4. The method for preparing a plastic admixture for vacuum extrusion molding of ridged vanadium tailings according to claim 2 or 3, characterized in that: In the step 2), the mixing speed is 15-30 r / min, and the mixing time is 20-40 min.
Citation Information
Patent Citations
Cellulose ether composition
US20070004826A1